Desafios E Perspectivas Nas Ciências Agrárias 2021
DOI: 10.35587/brj.ed.0001140
|View full text |Cite
|
Sign up to set email alerts
|

Utilização De Azospirillum Brasilense E Insumos Orgânicos Na Produção De Azevém Destinado À Cobertura Verde

Abstract: O conteúdo dos livros e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores. Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…This highlights the efficiency of biological fixation carried out by these bacteria and their nitrogen supply to plants. Similar results to this study were obtained by Oliveira (2019) and Caleffi (2021), who observed the contribution of Azospirillum brasilense in terms of nitrogen supply in ryegrass and irrigated rice development, respectively. According to Matos (2019), Azospirillum brasilense has the capacity to fix up to 30 kg N ha-1 when used in a single application.…”
Section: Resultssupporting
confidence: 92%
“…This highlights the efficiency of biological fixation carried out by these bacteria and their nitrogen supply to plants. Similar results to this study were obtained by Oliveira (2019) and Caleffi (2021), who observed the contribution of Azospirillum brasilense in terms of nitrogen supply in ryegrass and irrigated rice development, respectively. According to Matos (2019), Azospirillum brasilense has the capacity to fix up to 30 kg N ha-1 when used in a single application.…”
Section: Resultssupporting
confidence: 92%